Sex-specific endocrine regulation of seasonal aggression in Siberian hamsters. Issue 1982 (14th September 2022) - Munley, Kathleen M.; Trinidad, Jonathan C.; Demas, Gregory E.
Abstract : Coordinating physiological and behavioural processes across the annual cycle is essential in enabling individuals to maximize fitness. While the mechanisms underlying seasonal reproduction and its associated behaviours are well characterized, fewer studies have examined the hormonal basis of non-reproductive social behaviours (e.g. aggression) on a seasonal time scale. Our previous work suggests that the pineal hormone melatonin facilitates a 'seasonal switch' in neuroendocrine regulation of aggression in male and female Siberian hamsters ( Phodopus sungorus ), specifically by acting on the adrenal glands to increase the production of the androgen dehydroepiandrosterone (DHEA) during the short-day (SD) photoperiods of the non-breeding season. Here, we provide evidence that the activity of 3β-hydroxysteroid dehydrogenase/Δ5-Δ4 isomerase (3β-HSD), a key enzyme within the steroidogenic pathway that mediates DHEA synthesis and metabolism, varies in a sex-specific and melatonin-dependent manner. Although both male and female hamsters displayed increased aggression in response to SDs and SD-like melatonin, only males showed an increase in adrenal 3β-HSD activity. Conversely, SD and melatonin-treated females exhibited reductions in both adrenal and neural 3β-HSD activity. Collectively, these results suggest a potential role for 3β-HSD in modulating non-breeding aggression and, more broadly, demonstrate how distinct neuroendocrine mechanisms may underlie the same behavioural phenotype in males and females.